Enhancing Corporate Governance with Blockchain and Smart Contracts: A Systematic Review of Agency Conflict Mitigation - Arus Reka Prasetia; Primanola Perdananti; Ikaputera Waspada; Maya Sari (Moneta : Journal of Economics and Finance, 2026)
Agency conflicts remain a persistent challenge in corporate governance because information asymmetry and misaligned incentives can weaken monitoring and accountability. This systematic literature review synthesizes international empirical evidence on how blockchain and smart contracts relate to agency conflict mitigation and governance outcomes, and it clarifies boundary conditions and implications for Agency Theory. We followed PRISMA reporting guidance and searched Scopus for English journal articles published between 2018 and 2025. After title, abstract, and full-text screening, 13 empirical studies were included for quality appraisal and thematic narrative synthesis. Across contexts, blockchain adoption or innovation intensity is most consistently associated with improved information environments, including higher transparency and reporting quality and lower opportunism related proxies, and it is also associated with improved investment efficiency and selected compliance and risk outcomes. Evidence on smart contracts is substantially thinner. Smart contracts are explicitly analysed in one case study and they are discussed secondarily in one additional study, while none of the large sample quantitative studies operationalises smart contract use as a distinct construct. The synthesis indicates that governance benefits depend on data integrity supported by internal controls, external monitoring and assurance capacity, and regulatory and legal alignment that enables auditability and enforceability. Overall, blockchain-enabled corporate governance is best interpreted as governance by system design that complements conventional mechanisms and motivates future research on measurable smart contract use cases and stronger causal identification.